1985
DOI: 10.1002/chin.198509019
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: HYDRIDES BASED ON MAGNESIUM‐NICKEL‐LANTHANUM ALLOYS

Abstract: Untersucht wird die Reaktion von Wasserstoff mit einer Schmelze aus Mg, Ni und La.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The La 2 Ni 2 Mg crystallizes with a tetragonal structure, Mo 2 FeB 2 -type, determined by Hoffmann et al [26]. The crystal structure of the LaNiMg 2 , which shows a congruent formation at 630 • C [27], has been recently determined by Renaudin et al [7], who found an orthorhombic symmetry, CuMgAl 2 -type.…”
Section: Literature Data On the La-ni-mg Systemmentioning
confidence: 93%
“…The La 2 Ni 2 Mg crystallizes with a tetragonal structure, Mo 2 FeB 2 -type, determined by Hoffmann et al [26]. The crystal structure of the LaNiMg 2 , which shows a congruent formation at 630 • C [27], has been recently determined by Renaudin et al [7], who found an orthorhombic symmetry, CuMgAl 2 -type.…”
Section: Literature Data On the La-ni-mg Systemmentioning
confidence: 93%
“…The crystal structure and hydrogenation behavior of LaMg 2 Ni were studied by Kost et al [17] and Karonik et al [18,19]. Lately, the references demonstrated that LaMg 2 Ni reacts with hydrogen to form a quaternary metal hydride with a nominal composition of LaMg 2 NiH 7 at 1123 K, in addition, an amorphous phase is formed at * Corresponding author.…”
Section: Introductionmentioning
confidence: 98%
“…In order to improve the hydriding/dehydriding kinetics and plateau pressure performances for Mg 2 Ni, an approach of alloying with rare earths such as lanthanum has been attempted [12][13][14]. Thus, a new ternary magnesium-based compound, LaMg 2 Ni, was reported in recent years [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest is the orthorhombic LaMg 2 Ni phase of type MgAl 2 Cu (RG Cmcm) [15], which was only recently structurally characterised in detail by Renaudin et al [16]. From all La-Mg-Ni alloys investigated so far the LaMg 2 Ni phase shows the highest hydrogen absorption capacity.…”
Section: Introductionmentioning
confidence: 98%